Usefulness of Protocolized Point-of-Care Ultrasonography for Patients with Acute Renal Colic Who Visited Emergency Department: A Randomized Controlled Study - Kim, Seok Goo (Medicina (Kaunas), 2019)
Background and Objectives: Ultrasonography is useful in evaluating patients with renal colic and it has high sensitivity and specificity for diagnosing ureter stones by revealing hydronephrosis. We evaluated the efficacy of point-of-care ultrasonography protocol in managing patients with acute renal colic who visited the emergency department (ED). Materials and Methods: Between March 2019 and July 2019, patients who visited the ED because of renal colic were randomly assigned by date of visit either to the conventional group (CG), who underwent routine diagnostic work-up without ultrasonography, or to the ultrasonography group (UG), who underwent bedside ultrasonography as an initial diagnostic testing. When hydronephrosis was detected in the UG group, a confirmatory non-contrast abdomen computed tomography scan was promptly performed. The ED length of stay, complications, and missed or delayed high-risk diagnosis were evaluated. Results: In total, 128 of 147 analyzed patients were confirmed to have ureter stones. The ED length of stay was significantly lower in the UG group than in the CG group (mean 172 min; 95% confidence interval (CI): 151–194 min vs. mean 234 min; 95% CI: 216–252 min). The medical cost was also remarkably lower in the UG group than in the CG group (259 USD vs. 319 USD; p < 0.001). The incidence of complications within 30 days after visiting ED and missed or delayed high-risk diagnosis were not significantly different between the two groups. Conclusions: We found that protocolized point-of-care ultrasonography in patients with acute renal colic who visited the ED can more effectively reduce the length of stay and medical cost without 30-day complication than usual clinical practice.